The Role of Parents in Enhancing Children's Religious Behavior - Mufidah, Luluk Indarinul; Duror, Anirotud; Sobirin, Sobirin; Fawait, Agus; Irsyadiah, Nur (STAI Miftahul Ula Nganjuk, 2024)
This study aims to explore the role of parents in enhancing religious behavior, with a specific focus on worship discipline at home, and to examine their contribution to improving children's religious behavior, particularly in fostering commendable character (akhlaq). The research employs a qualitative approach using a descriptive case study methodology, which involves the detailed and in-depth collection of data concerning a particular individual or group. Data were gathered through observations, interviews, and documentation, and analyzed through the processes of data collection, reduction, and conclusion drawing. The findings indicate that the role of parents in enhancing religious behavior, particularly in promoting worship discipline, has been effectively implemented. Parents serve as both educators and supervisors, guiding their children in fulfilling religious obligations. Furthermore, the study highlights the importance of the family as a key environment for the development of religious behavior, with parents acting as role models in instilling religious values. The research emphasizes that the active involvement of parents in nurturing worship discipline and good character contributes significantly to shaping children's religious behavior, ensuring that these values are embedded both at home and in their daily lives. This study underscores the critical role of parents in the religious and moral development of their children, particularly in the formative years